Systemic Inflammation Associated With World Trade Center Dust Exposures and Airway Abnormalities in the Local Community. Issue 6 (June 2015) - Kazeros, Angeliki; Zhang, Enhan; Cheng, Xin; Shao, Yongzhao; Liu, Mengling; Qian, Meng; Caplan-Shaw, Caralee; Berger, Kenneth I.; Goldring, Roberta M.; Ghumman, Muhammad; Chokshi, Neel P.; Levy-Carrick, Nomi; et al.
Abstract : Background: Destruction of the World Trade Center (WTC) towers on September 11, 2001, released massive dust, gas, and fumes with environmental exposures for community members. Many community members have lower respiratory symptoms (LRSs) that began after September 11, 2001, and remain persistent. We evaluated whether systemic inflammation measured by C-reactive protein was associated with WTC dust exposures, persistent LRS, and lung function. Methods: Community members self-referred for the treatment of symptoms related to September 11, 2001. C-reactive protein and lung function measurements, including spirometry and forced oscillation tests (impulse oscillometry system), were included as routine analyses in patients (2007 to 2012). Results: Increased C-reactive protein levels were associated with the type of WTC dust exposure, LRS, reduced spirometry, and increased forced oscillation measurements ( n = 724). Conclusions: Ongoing systemic inflammation measured years after the event was associated with WTC dust exposures, persistent LRS, and abnormal lung function in a community cohort. These findings have implications for treatment and surveillance.